Tissue- and hormone- dependent progesterone receptor distribution in the rat uterus - Sahlin Lena; Masironi Britt; Åkerberg Sonja; Eriksson Håkan (BMC, 2006)
Abstract Background Estradiol (E2) and progesterone (P) are well known regulators of progesterone receptor (PR) expression in the rat uterus. However, it is not known which receptor subtypes are involved. Little knowledge exist about possible differences in PR regulation through ERalpha or ERbeta, and whether the PR subtypes are differently regulated depending on ER type bound. Thus, in the present study PR immunostaining has been examined in uteri of ovariectomized (ovx) rats after different treatments of estrogen and P, in comparison with that in immature, cycling, and pregnant animals. Methods The uteri were collected from 1) ovx rats treated with E2 and/or P; 2) immature rats, intact cycling rats and animals pregnant day 8 and 18; 3) ovx rats treated with E2 or an estrogen receptor (ER)alpha agonist or an ERbeta agonist. Two antibodies were used, one detecting PRA+B and another one specific for PRB. Real-time PCR was used to determine mRNA levels for PRAB and PRB in experiment 3. Results In stroma and myometrium faint staining was detected in ovx controls (OvxC), whereas E2 treatment resulted in strong staining. In contrast to this, in luminal epithelium (LE) the staining was strong in the OvxC group, whereas E2 treatment during the last 24 hrs before sacrifice caused a decrease. Similar to OvxC the LE of the immature animals was strongly stained. In the pregnant rats LE was negative, well in agreement with the results seen after E2 treatment. In the pregnant animals the stroma and decidua was strongly stained for PRAB, but only faint for PRB, indicating that PRA is the most expressed isoform in this state. The increase in stromal and myometrial immunostaining after E2 treatment was also found after treatment with the ERalpha agonist PPT. The ERbeta agonist DPN caused a decrease of the PR mRNA levels, which was also found for PRAB and PRB immunostaining in the GE. Conclusion Stromal and myometrial PRAB levels are increased via ERalpha, as shown by treatment with E2 and the ERalpha agonist PPT, while the levels in LE are decreased. The uterine stroma of pregnant rats strongly expressed PRAB, but very little PRB, which is different to E2 treated ovx animals where both PRAB and PRB are strongly expressed. The ERbeta agonist DPN decreased the mRNA levels of PRAB and PRB, as well as the PRAB protein level in GE. These results suggest that ERbeta signals mainly down-regulate PR levels in the epithelial cells. ERalpha, on the other hand, up-regulates PR levels in the stroma and myometrium while it decreased them in LE. Thus, the effects from E2 and PPT on the mRNA levels, as determined by PCR, could be annihilated since they are increased and decreased depending on cell type. The distribution and amount of PR isoforms strongly depend on the hormonal milieu and cell type within the rat uterus.